ACCELERATED STABILITY STUDY AND MICROBIOLOGICAL TESTS ON NEW ORAL MATRIX DELIVERY SYSTEMS FOR DICLOFENAC SODIUM - Abdalla Gargar, Abdalla A.; Elnima, Elamin Ibrahim; Abdulkarim, Abdulkarim M. (Gezira Journal of Health Sciences; Vol 2 No 2 (2006), 2006)
An accelerated stability study was performed on diclofenac sodium controlled release matrix tablets (MT20,MT33,MT34,MT33p,MT34p ) containing natural gums, semi-synthetic gum , Eudragit L100,and hydroxypropylmethylcellulose (HPMC).Drug content was found to be in the range of 90-105% in all the five matrix formulas. Applying out of stability trend rules (OOT), the best formula was found to be MT33 which contained Guar gum 15%, and gum Arabic15%. No changes in physical appearance, or organoleptic properties were observed. Microbiological tests for the five matrix tablets were evaluated (1) . No growth (bacteria or fungi) was detected, in preserved or non-preserved formulas despite of the gum content in these controlled release tablets